Genetic risk of extranodal natural killer T-cell lymphoma: a genome-wide association study in multiple populations. Issue 2 (February 2020) - Lin, Guo-Wang; Xu, Caigang; Chen, Kexin; Huang, Hui-Qiang; Chen, Jieping; Song, Bao; Chan, John K C; Li, Wenyu; Liu, Weiping; Shih, Lee-Yung; Chuang, Wen-Yu; Kim, Won Seog; et al.
Summary: Background: Extranodal natural killer T-cell lymphoma (NKTCL; nasal type) is an aggressive malignancy with a particularly high prevalence in Asian and Latin American populations. Epstein-Barr virus infection has a role in the pathogenesis of NKTCL, and HLA-DPB1 variants are risk factors for the disease. We aimed to identify additional novel genetic variants affecting risk of NKTCL. Methods: We did a genome-wide association study of NKTCL in multiple populations from east Asia. We recruited a discovery cohort of 700 cases with NKTCL and 7752 controls without NKTCL of Han Chinese ancestry from 19 centres in southern, central, and northern regions of China, and four independent replication samples including 717 cases and 12 650 controls. Three of these independent samples (451 cases and 5301 controls) were from eight centres in the same regions of southern, central, and northern China, and the fourth (266 cases and 7349 controls) was from 11 centres in Hong Kong, Taiwan, Singapore, and South Korea. All cases had primary NKTCL that was confirmed histopathologically, and matching with controls was based on geographical region and self-reported ancestry. Logistic regression analysis was done independently by geographical regions, followed by fixed-effect meta-analyses, to identify susceptibility loci. Bioinformatic approaches, including expression quantitative trait loci, binding motif and transcriptome analyses, and biological experiments were done to fine-map and explore the functional relevance of genome-wide association loci to the development of NKTCL. Findings: Genetic data were gathered between Jan 1, 2008, and Jan 23, 2019. Meta-analysis of all samples (a total of 1417 cases and 20 402 controls) identified two novel loci significantly associated with NKTCL: IL18RAP on 2q12.1 (rs13015714; p=2·83 × 10 −16 ; odds ratio 1·39 [95% CI 1·28–1·50]) and HLA-DRB1 on 6p21.3 (rs9271588; 9·35 × 10 −26 1·53 [1·41–1·65]). Fine-mapping and experimental analyses showed that rs1420106 at the promoter of IL18RAP was highly correlated with rs13015714, and the rs1420106-A risk variant had an upregulatory effect on IL18RAP expression. Cell growth assays in two NKTCL cell lines (YT and SNK-6 cells) showed that knockdown of IL18RAP inhibited cell proliferation by cell cycle arrest in NKTCL cells. Haplotype association analysis showed that haplotype 47F-67I was associated with reduced risk of NKTCL, whereas 47Y-67L was associated with increased risk of NKTCL. These two positions are component parts of the peptide-binding pocket 7 (P7) of the HLA-DR heterodimer, suggesting that these alterations might account for the association at HLA-DRB1, independent of the previously reported HLA-DPB1 variants. Interpretation: Our findings provide new insights into the development of NKTCL by showing the importance of inflammation and immune regulation through the IL18–IL18RAP axis and antigen presentation involving HLA-DRB1, which might help to identify potential therapeutic targets. Taken in combination with additional genetic and other risk factors, our results could potentially be used to stratify people at high risk of NKTCL for targeted prevention. Funding: Guangdong Innovative and Entrepreneurial Research Team Program, National Natural Science Foundation of China, National Program for Support of Top-Notch Young Professionals, Chang Jiang Scholars Program, Singapore Ministry of Health's National Medical Research Council, Tanoto Foundation, National Research Foundation Singapore, Chang Gung Memorial Hospital, Recruitment Program for Young Professionals of China, First Affiliated Hospital and Army Medical University, US National Institutes of Health, and US National Cancer Institute.